Las publicaciones sobre estudios de cine y medios irlandeses 2022 - Ciara Chambers (Estudios Irlandeses, 2023)
Even before the birth of cinema, literary and visual forms of cultural creation and expression had a rich history of intertextual interaction. This year’s section includes reviews of two books (one monograph and one edited collection) with a heavy focus on literature alongside some illuminating scholarship on visual forms. Both books also deal with Irish identity and masculinity on a local and world stage. The first is Val Nolan’s study of Neil Jordan, a towering figure in Irish cinema, known internationally for work made both in Ireland and in Hollywood. Neil Jordan: Words for the Page explores Jordan’s writing, a largely underscrutinised area in scholarly critique (which has mostly focussed on his cinematic output). Jordan has always been a literary filmmaker: in some cases his screenplays are based on literary sources he has adapted himself, on other occasions he works with notable authors as writing collaborators. As Gough points out, Nolan demonstrates how Jordan’s writing explores literary traditions in tandem with his filmmaking, and it is this approach that secures Jordan’s reputation as one of Ireland’s leading “multi-faceted creative[s]”.